2020
DOI: 10.5194/acp-20-13217-2020
|View full text |Cite
|
Sign up to set email alerts
|

Environmental sensitivities of shallow-cumulus dilution – Part 1: Selected thermodynamic conditions

Abstract: Abstract. Cumulus entrainment, and its consequent dilution of buoyant cloud cores, strongly regulates the life cycle of shallow cumuli yet remains poorly understood. Herein, new insights into this problem are obtained through large-eddy simulations that systematically investigate the sensitivity of shallow-cumulus dilution to cloud-layer relative humidity (RH), cloud- and subcloud-layer depths, and continentality (i.e., the land–ocean contrast). The simulated cloud-core dilution is found to be strongly sensiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 75 publications
1
23
0
Order By: Relevance
“…As in Part I of this study, we conduct LES of shallow cumulus ensembles using the Bryan Cloud Model version 17 (CM1; Bryan and Fritsch, 2002). In LES mode, CM1 accurately reproduces the findings from past LES inter-comparison studies of shallow cumuli (Drueke et al, 2019(Drueke et al, , 2020. To examine diverse cloud fields, we consider one maritime case and one continental case, the former based on the LES inter-comparison study of the Barbados Oceanographic and Meteorological Experiment (BOMEX) by Siebesma et al (2003), and the latter based on the LES inter-comparison of shallow cumuli at the US Atmospheric Radiation Measurement (ARM) Southern Great Plains (SGP) observatory in Oklahoma (Brown et al, 2002).…”
Section: Model Configurationmentioning
confidence: 73%
See 4 more Smart Citations
“…As in Part I of this study, we conduct LES of shallow cumulus ensembles using the Bryan Cloud Model version 17 (CM1; Bryan and Fritsch, 2002). In LES mode, CM1 accurately reproduces the findings from past LES inter-comparison studies of shallow cumuli (Drueke et al, 2019(Drueke et al, , 2020. To examine diverse cloud fields, we consider one maritime case and one continental case, the former based on the LES inter-comparison study of the Barbados Oceanographic and Meteorological Experiment (BOMEX) by Siebesma et al (2003), and the latter based on the LES inter-comparison of shallow cumuli at the US Atmospheric Radiation Measurement (ARM) Southern Great Plains (SGP) observatory in Oklahoma (Brown et al, 2002).…”
Section: Model Configurationmentioning
confidence: 73%
“…This finding can be explained by a simple buoyancy-sorting argument. Drueke et al (2020) also found a strong sensitivity of shallowcumulus dilution to continentality, in that simulated maritime cumuli experienced about twice the dilution of corresponding continental cumuli. The sensitivity was linked to larger cloud-base mass fluxes over land, driven by stronger sensible heat fluxes and subcloud turbulence.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations